2013
DOI: 10.1016/j.bjid.2013.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus in the State of Alagoas, Brazil: genotypes characterization and mutations of the precore and basal core promoter regions

Abstract: The aims of this study were to investigate the genotypes of hepatitis B virus and to identify the precore G1896A and basal core promoter A1762T/G1764A mutations in HBsAg and anti-HBc-positive patients. Eighty-three asymptomatic individuals, three with acute hepatitis B and 33 with chronic hepatitis B referred to viral hepatitis centers in the State of Alagoas, Brazil were analyzed according to their viral load, HBeAg/anti-HBe profile and alanine aminotransferase serum level. The genotypes identified were: A (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Similarly to our results, genotype A was the most frequent in the Northeast region [19], while genotypes A and D were reported as the most frequent in the south and southeast regions [20,21].…”
Section: Discussionsupporting
confidence: 91%
“…Similarly to our results, genotype A was the most frequent in the Northeast region [19], while genotypes A and D were reported as the most frequent in the south and southeast regions [20,21].…”
Section: Discussionsupporting
confidence: 91%
“…HBV continues to be the most important aetiological agent of acute viral hepatitis, fulminant hepatitis, chronic hepatitis, liver cirrhosis and hepatocellular carcinoma in the developing and underdeveloped world. HBV is prone to mutations with nucleotide substitutions estimated at a rate of 1 × 10 −5 to 3 × 10 −5 per site per year (Eloy et al, 2013). Mutations have been detected in all the regions of the HBV genome but the significance of many of these mutations is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, we revealed the strong association between multiple mutations at nt 1762/1764/1896/1899 and HBeAg seroconversion, which was supported by the findings that 1762/1764 double mutations repress HBeAg precursor expression [37]. The 1896G>A nonsense mutation terminates HBeAg expression by creating a stop codon [33], and the 1899G>A results in a missense mutation that inhibits the recognition and cleavage of HBeAg precursor by related enzymes [38], which eventually led to intracellular accumulation of HBeAg and its negativity in serum [39, 40]. Therefore, it could be concluded that those multiple mutations in RT and BCP-PreC region were not able to detect HBeAg and never impeded HBV replication, and therefore this led to a spurious HBeAg negativity.…”
Section: Discussionmentioning
confidence: 61%
“…The BCP-PreC/C region is another important genetic area not only because it encodes proteins that are integral for HBV structure and functions but also because it is vulnerable to mutations that are associated with liver function injury and progression to HCC [5, 32]. Mutations at nt 1762, 1764, 1766, and 1768 located in BCP region have been reported to be associated with interferon-resistance and liver function injury [33]. Consistently, our data showed that double mutations at nt 1762/1764 were a significant risk factor of liver injury featured by elevated serum ALT and AST levels.…”
Section: Discussionmentioning
confidence: 99%